2023
DOI: 10.3390/app13095668
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antimicrobial Effect of Photodynamic Inactivation and SWEEPS in Combined Treatment against Enterococcus faecalis in a Root Canal Biofilm Model: An In Vitro Study

Abstract: Background: Persistent bacterial infections caused by biofilm-associated Enterococcus faecalis are a global public health concern. This study aims to compare the biofilm removal effects of methylene blue (MB) or hydrogen peroxide (HP) mediated photodynamic inactivation (PDI) with a shock wave enhanced emission photoacoustic streaming (SWEEPS) method laser irradiation enhanced bactericidal activity. Methods: A total of fifty extracted single-rooted human teeth were used. Each canal was then inoculated with a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…Consistent with the present results, previous studies also showed that application of SWEEPS with a 660 and 980 nm diode laser or light-emitting diode (LED) can cause a more significant decrease in the root canal infected with E. faecalis [25,30]. However, in contrast with the results of this study, the diode laser and SWEEPS did not show significant differences with methylene blue in their use as a photosensitizer [30]. Since the type of photosensitizer, light source, and irradiation time affect the bactericidal properties, this difference might be related to the fact that the mechanism of action of ICG is different from that of other photosensitizers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the present results, previous studies also showed that application of SWEEPS with a 660 and 980 nm diode laser or light-emitting diode (LED) can cause a more significant decrease in the root canal infected with E. faecalis [25,30]. However, in contrast with the results of this study, the diode laser and SWEEPS did not show significant differences with methylene blue in their use as a photosensitizer [30]. Since the type of photosensitizer, light source, and irradiation time affect the bactericidal properties, this difference might be related to the fact that the mechanism of action of ICG is different from that of other photosensitizers.…”
Section: Discussionsupporting
confidence: 92%
“…The SWEEPS technique mechanically detaches the biofilm from the root canal, therefore increasing the penetration depth and efficacy of the photosensitizer, due to the frequent generation of cavitation [1]. Consistent with the present results, previous studies also showed that application of SWEEPS with a 660 and 980 nm diode laser or light-emitting diode (LED) can cause a more significant decrease in the root canal infected with E. faecalis [25,30]. However, in contrast with the results of this study, the diode laser and SWEEPS did not show significant differences with methylene blue in their use as a photosensitizer [30].…”
Section: Discussionsupporting
confidence: 89%
“…Deeper penetration into biofilms as well as low interference from radiation are the advantages of HP [20]. The use of HP as a photosensitizer has been investigated in several studies [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this work was to fabricate two different narrow confined geometries and compare the efficiency of two laser pulse modalities for biofilm removal. We hypothesized that Er:YAG-AutoSWEEPS photoacoustic irrigation would better reach inaccessible sites and increase fluid flow rate in narrow geometries which would in turn increase the cleaning of Enterococcus faecalis biofilms, the main causative agent of persistent bacterial infection in oral cavity [ 36 , 37 , 38 , 39 ]. Biofilms were grown on titanium disks of different dimensions for 3 days to reach maturity.…”
Section: Introductionmentioning
confidence: 99%